(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes the political, economic and ideological goals of Soviet power in the years 1953-1956 in the propaganda work of Uzbekistan in the USSR, including the use of the press, in particular, newspapers, along with the directions of the work